2004
DOI: 10.1149/1.1753231
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Al-Zr Alloys from Lewis Acidic Aluminum Chloride-1-Ethyl-3-methylimidazolium Chloride Melt

Abstract: The electrochemistry of Zr͑IV͒ and Zr͑II͒ and the electrodeposition of Al-Zr alloys were examined in the Lewis acidic 66.7-33.3 mol % aluminum chloride-1-ethyl-3-methylimidazolium chloride molten salt at 353 K. The electrochemical reduction of Zr͑IV͒ to Zr͑II͒ is complicated by the precipitation of ZrCl 3 ; however, solutions of Zr͑II͒ can be prepared by reducing Zr͑IV͒ with Al wire. Al-Zr alloys can be electrodeposited from plating baths containing either Zr͑IV͒ or Zr͑II͒, but for a given concentration and cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 44 publications
4
56
0
1
Order By: Relevance
“…This behavior simply reflects the fact that the anionic speciation in these ILs varies with the components' ratio. A large variety of metals and their alloys that cannot electrodeposit in conventional aqueous or organic solvents, e.g., Al, [102][103][104][105][106][107][108] Li, [109][110][111][112][113][114][115] Na, [109,[111][112][113]116,117] La, [114] AlÀMg, [118] AlÀTi, [119][120][121] AlÀZr, [122] AlÀHf, [123] AlÀV, [124] AlÀNb, [125] AlÀCr, [126][127][128][129][130][131] AlÀMo, [132] AlÀW, [123] AlÀMn, [133,134] NbÀSn, [135] AlÀNiÀCr, [136] AlÀNiÀMo, [137] AlÀMoÀMn, [138] AlÀInÀSb, [139] AlÀMoÀTi, [140] are produced from those ILs. Most deposits are nonequilibrium Al alloys.…”
Section: Electrodeposition Of Metallic/semiconducting Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This behavior simply reflects the fact that the anionic speciation in these ILs varies with the components' ratio. A large variety of metals and their alloys that cannot electrodeposit in conventional aqueous or organic solvents, e.g., Al, [102][103][104][105][106][107][108] Li, [109][110][111][112][113][114][115] Na, [109,[111][112][113]116,117] La, [114] AlÀMg, [118] AlÀTi, [119][120][121] AlÀZr, [122] AlÀHf, [123] AlÀV, [124] AlÀNb, [125] AlÀCr, [126][127][128][129][130][131] AlÀMo, [132] AlÀW, [123] AlÀMn, [133,134] NbÀSn, [135] AlÀNiÀCr, [136] AlÀNiÀMo, [137] AlÀMoÀMn, [138] AlÀInÀSb, [139] AlÀMoÀTi, [140] are produced from those ILs. Most deposits are nonequilibrium Al alloys.…”
Section: Electrodeposition Of Metallic/semiconducting Materialsmentioning
confidence: 99%
“…Some aluminum alloys prepared from ILs form amorphous glass phases. [122,[126][127][128][129][130][131][132][133][134][136][137][138] The properties of the aluminum alloys resulting from the electrodeposition process are virtually identical to those prepared by conventional nonequilibrium alloying methods, e.g., sputtering, melt spinning, plasma spraying, and ion implantation. These coatings show excellent corrosion resistance compared to pure Al.…”
Section: Electrodeposition Of Metallic/semiconducting Materialsmentioning
confidence: 99%
“…These alloys are formed at or less than 0 V vs. Al(III)/Al without difficulty. Many Al alloy systems have been prepared by this route, including Al-Mg, 77 Al-Ti, [78][79][80] Al-Zr, 81 AlHf, 72 Al-V, 82 Al-Cr, [83][84][85][86][87][88] Al-Mo, 89 Al-W, 73 Al-Mn, 90,91 Al-In, 74 and Al-La. 44 It has been determined by X-ray diffraction techniques that Al-Zr, Al-Cr, Al-Mo, Al-W and Al-Mn in particular form amorphous glass phases.…”
Section: Electrodeposition Aluminum Alloys From Haloaluminate Rtilsmentioning
confidence: 99%
“…A representative ionic liquid used for the electrodeposition of Al alloys is Lewis acidic 1-ethyl-3-methylimidazolium chloride (EMIC)-AlCl 3 (where the AlCl 3 /EMIC molar ratio >1). Reports on the electrodeposition of Al alloys including Al-Ni, 13 Al-Ti, 14 Al-V, 15 Al-Zr, 16 Al-Mo, 17 Al-Mn, 18 and Al-Hf 19 are available in the literature. A previous study revealed that electrodeposition in a EMIC-AlCl 3 bath with the addition of W(IV) chloride (WCl 4 ) yielded Al-W alloys, but the W content was lower than 1 at.%.…”
mentioning
confidence: 99%